A 15-year pathologic review of testicular and para-testicular tumours in Kano, Northern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Testicular and para-testicular tumours are envisaged as being rare in our setting. However, there is no published report on their statistics from Kano, Northern Nigeria despite the reported gradual increase over the past decades in many communities.Aim:The purpose of this study, therefore, is to determine the prevalence among other tumours, the frequency and the morphological patterns of testicular and para-testicular tumours in Kano, Northern Nigeria.Materials and Methods:This was a 15-year retrospective study of all cases of testicular and para-testicular tumours histologically diagnosed at Aminu Kano Teaching Hospital, from January 2001 to December 2015. Where necessary, new tissue sections were reprocessed from the formalin-fixed, paraffin-embedded blocks.Results:There were a total of 31 cases of testicular and para-testicular tumours recorded during the study period with an average incidence of 2 cases per year; 41.9% of these were testicular tumours and 58.1% para-testicular tumours. The youngest patient was 3 years old, whereas the oldest was 49 years. Among the para-testicular tumours, 27.8% were adenomatoid tumours mostly presenting in the fourth decade of life; followed by the embryonal rhabdomyosarcomas in 16.7% of cases all in children.Conclusion:This study attested to the low prevalence of testicular and para-testicular tumours in our environment and the findings conforms with studies from other African, the Caribbean and Asia communities but shows divergence to the western societies where a much higher prevalence was reported.